2018
DOI: 10.1111/ijal.12246
|View full text |Cite
|
Sign up to set email alerts
|

“We are not the language police”: Comparing multilingual EMI programmes in Europe and Asia

Abstract: English medium instruction (EMI) in higher education has rapidly increased over the last decade in Europe and Asia. However, this expansion has far outstripped research and many key questions remain unanswered. This study addresses a number of those questions related to roles and conceptualisations of English and other languages in multilingual university settings. Data is presented from an exploratory mixed‐methods (121 questionnaire responses and 12 interviews with lecturers and students), comparative study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 23 publications
2
28
0
Order By: Relevance
“…(1) JAI: because I don't really have the training/to be able to correct eh?/or to know when it's may should or an ought to /I think that's the job of you/I mean people who really have a superior linguistic knowledge/but I don't know if I'm doing things the right way eh?/ GER: there is no formula/what do you think would be the formula so that the student/finished the subject of/so well/receiving this feedback on this should or may that you are talking about right? JAI: of course in that case/yes I do/what I've told them is I'm not going to do/to correct anything of their English/and they only have to use use/I mean that they use English that they can understand/the English that is being communicated/ and that they know how to transmit a little INT: okay JAI: but without going beyond that/without going into the grammar/ GER: you mean the goal is comprehension right?/the goal is comprehension DER: and as for the part that's production/that would be in an English class/an English class/ JAI: yes/ DER: grammar would be working on/lexis/ JAI: yes/ DER: the pronunciation/and you concentrate on lexis especially right?/ because that's where/ JAI: I concentrate on lexis/but of course that's because pronunciation (1) I also have my deficits/and then it also depends on the source you go to/so in a video I see that an American pronounces it one way/ you go to the video of a British person/and then yes/there are basic things that/ DER: right right/ JAI: but I don't/I don't feel ABLE to correct anyone/aspects of pronunciation/ DER: okay/ GER: why do you think there is … a single way of saying it … correctly?/ JAI: NO no no/…/I know that there are many ways/…/but I understand that/well with my training/I can't do much/ (Jaime, 7 March 2017; author's translation for original in Spanish)In this exchange, Jaime rejects attempts by the interviewers, Gerard and Derek, to position him as a language teacher, thus resisting the ELT gaze driving their comments. His behaviour here echoes findings in other contexts, where EMI lecturers reject outright that they might act in a language teaching capacity (Airey, 2012; Baker & Hüttner, 2019). He emphasises in turn 1 that he does a minimum of work on oral and written communication, and then in turn 7, he establishes a disciplinary distinction, stating that unlike the interviewers, he is not qualified as an English teacher – not having ‘superior linguistic knowledge’.…”
Section: Self-positioning As Emi Lecturers But Not Language Teacherssupporting
confidence: 83%
“…(1) JAI: because I don't really have the training/to be able to correct eh?/or to know when it's may should or an ought to /I think that's the job of you/I mean people who really have a superior linguistic knowledge/but I don't know if I'm doing things the right way eh?/ GER: there is no formula/what do you think would be the formula so that the student/finished the subject of/so well/receiving this feedback on this should or may that you are talking about right? JAI: of course in that case/yes I do/what I've told them is I'm not going to do/to correct anything of their English/and they only have to use use/I mean that they use English that they can understand/the English that is being communicated/ and that they know how to transmit a little INT: okay JAI: but without going beyond that/without going into the grammar/ GER: you mean the goal is comprehension right?/the goal is comprehension DER: and as for the part that's production/that would be in an English class/an English class/ JAI: yes/ DER: grammar would be working on/lexis/ JAI: yes/ DER: the pronunciation/and you concentrate on lexis especially right?/ because that's where/ JAI: I concentrate on lexis/but of course that's because pronunciation (1) I also have my deficits/and then it also depends on the source you go to/so in a video I see that an American pronounces it one way/ you go to the video of a British person/and then yes/there are basic things that/ DER: right right/ JAI: but I don't/I don't feel ABLE to correct anyone/aspects of pronunciation/ DER: okay/ GER: why do you think there is … a single way of saying it … correctly?/ JAI: NO no no/…/I know that there are many ways/…/but I understand that/well with my training/I can't do much/ (Jaime, 7 March 2017; author's translation for original in Spanish)In this exchange, Jaime rejects attempts by the interviewers, Gerard and Derek, to position him as a language teacher, thus resisting the ELT gaze driving their comments. His behaviour here echoes findings in other contexts, where EMI lecturers reject outright that they might act in a language teaching capacity (Airey, 2012; Baker & Hüttner, 2019). He emphasises in turn 1 that he does a minimum of work on oral and written communication, and then in turn 7, he establishes a disciplinary distinction, stating that unlike the interviewers, he is not qualified as an English teacher – not having ‘superior linguistic knowledge’.…”
Section: Self-positioning As Emi Lecturers But Not Language Teacherssupporting
confidence: 83%
“…Although in the survey students and faculty members generally evaluated their English proficiency rather highly, during the interviews they stated that they code‐switched during the lessons. Most research studies report that code‐switching mainly happens when there is a misunderstanding or for the necessity to clarify certain points (Baker & Hüttner, 2018; Macaro et al., 2018; Tarnopolsky & Goodman, 2014). Both aspects were evidenced in the findings of this study as well.…”
Section: Discussionmentioning
confidence: 99%
“…A recent international survey, conducted through 79 universities found that the pedagogy for EMI teaching was "far from being treated as an important issue" and there was not "sufficient attention to the training and accreditation of the teachers engaged in EMI" [27] (p. 557). Most universities offering a significant number of subjects through EMI, admitted that they did not provide training for their EMI lecturers [16,27,57]. Nevertheless, a couple of studies among these do report on methodological programs.…”
Section: Pedagogical Issues In Emi Teachingmentioning
confidence: 99%